Stented Lich-Gregoir Ureteroneocystostomy in renal transplantation: an experience at Bangabandhu Sheikh Mujib Medical University in Bangladesh - Ullah, ATM A; Hossain, M; Hooda, MN; Islam, MS; Haque, MM; Alam, AKM K; Islam, AKM A; Kibria, SAM G (Bangladesh Journal of Urology, 2020)
Ureteral reimplantation is one of the important components of reconstruction of urinary tract in renal transplantation. There are various techniques of ureteral reimplantation, of which Extravesical Lich-Gregoir is the ideal technique for renal transplantation. Extravesical ureteroneocystostomy to reestablish urinary tract continuity in renal transplantation has been examined through a study of 140 kidney transplants leading to the finding that stented anastomosis was associated with a lower urologic complication rate. We now report the urologic complication rate in our case series in which stented Lich–Gregoir anastomosis was routinely utilized. Methods. The records of 140 consecutive renal transplants were reviewed. Minimum follow-up time was 3 months. The standard anastomosis was a Lich–Gregoir with a 5-6 Fr cm D-J stent. Monitored urologic complications included postoperative vesicoureteral leak or ureteral necrosis, obstruction or stricture, or clinically significant hematuria. Results. One urologic complication were noted—one leak and no other complication. There were no stentrelated complications requiring reoperation. There were no cases in which the urologic complication led to graft loss or patient death. Conclusions. The urologic complication rate in this case series is less to the five previously published randomized trials, as well as our previous study. These results support the routine use of a ureteral stent Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.48-50